Bronchodilator responsiveness in cystic fibrosis children treated for pulmonary exacerbations. Issue 7 (20th April 2021) - Pollak, Mordechai; Shaw, Michelle; Wilson, David; Solomon, Melinda; Ratjen, Felix; Grasemann, Hartmut
Abstract: Background: Cystic fibrosis (CF) pulmonary exacerbations (PEx) are associated with a significant drop in pulmonary function. The clinical value of measuring bronchodilator (BD) responsiveness during treatment for PEx to monitor or predict recovery of lung function is unclear. Methods: A retrospective analysis of spirometry with BD response testing obtained during hospital admissions for PEx in pediatric CF patients. Repeated events were included for patients with BD testing during multiple admissions. Results: Two hundred forty‐nine spirometries with BD testing in 102 patients were completed around Day 7 (Days 4–10) of hospital admission for treatment of CF PEx. Median (IQR) forced expiratory volume in 1 s (FEV1 ) was 70.6% predicted (58.1, 84.6) before the PEx event (best FEV1 in 6 months before admission), 54.4% (41.5, 66.9) at admission, 62.3% (48.4, 74.7) around Day 7 of admission and 67.1% predicted (53.8, 78.2) at the end of treatment. BD response around Day 7 correlated poorly with FEV1 before PEx ( r = −.16, p = .02) and did not correlate with recovery to baseline FEV1 at end of treatment ( r = .08, p = .22). Only 23/249 (9%) individual tests had a BD response in FEV1 of ≥12% and 200 ml. BD response was not related to age or severity of lung disease and led to an immediate change in clinical management in only four cases. Conclusions: Significant BD response in CF patients treated for PEx is rare, shows poor correlation with baseline pulmonary function and does not correlate with the recovery of FEV1 with treatment. These data suggest that routine testing for BD response is not indicated during PEx.